ANTIMICROBIAL ACTIVITY AND ENZYMES ON SKIN MUCUS FROM MALE AND FEMALE CASPIAN KUTUM (Rutilus frisii kutum Kamensky, 1901) SPECIMENS - Milad Adel; Reza Safari; Siyavash Soltanian; Mohammad Jalil Zorriehzahra; Maria Ángeles Esteban (Slovenian Veterinary Research, 2018)
The mucus layer covering the surface of fish contain a high number of antimicrobial compounds that provide a first line of defense against aquatic pathogens. In the present study, bactericidal activity present on skin mucus of Caspian kutum (Rutilus frisii kutum) broodstock was tested against six pathogenic bacterial strains (Streptococcus iniae, Yersinia ruckeri, Staphylococcus aureus, Listeria monocytogenes, Pseudomonas aeruginosa and Escherichia coli). Furthermore, fungicidal activity was assessed against four pathogenic fungi (Saprolegnia sp., Fusarium solani, Candida albicans and Aspergillus flavus). Maximum and minimum antibacterial activity was observed against Y. ruckeri and S. iniae, respectively, while maximum and minimun fungicidal activty was detected against F. solani and C. albicans, respectively. Curiously, antimicrobial activity was higher in the fish mucus of female than male against most tested strains. In addition, minimum inhibitory concentration test showed that minimum concentrations of mucus ranged between 125 to 500 μg/L were able to inhibit the growth of the selected bacterial and fungal pathogens. Alkaline phosphatase, lysozyme, protease and esterase activities were also studied on mucus samples being the observed activities very similar between both sexes, although higher lysozyme activity was detected in the mucus of female fish in comparison to the values recorded on male samples. Skin mucus of this fish species (especially females) could be a potential source of newer and more effective antibacterial components.